Nilai Moral Dalam Novel Si Anak Savana Karya Tere Liye - Alva Olina S, Yesika; Rahayu, Sri (UIR Press, 2023)
Moral value is a value that must be possessed by every human being. Moral is very important to be able to judge one's life in society. Likewise, in a novel, moral values will be very important to assess the characters and the lives of these characters and the moral values themselves will be seen in the daily lives of the characters. The problem studied in this study is how are the moral values contained in the novel Si Anak Savana by Tere Liye. The purpose of this research is to describe, analyze, interpret and collect data about moral values in the novel Si Anak Savana by Tere Liye from the aspects of responsibility, conscience and obligations. The source of the data is the entire content of the novel Si Anak Savana by Tere Liye. The approach used is a qualitative approach to the type of library research. The method used is descriptive method. The data collection technique used was the hermeneutic technique, while the data analysis technique used content analysis technique. Based on the results of the discussion in this study, it can be concluded that there are 5 data aspects of responsibility that can be seen from the attitudes of the characters in the novel who consistently adhere to the noble values of Kampung Dopu, that is, being responsible for the slightest task assigned, the mandate that is carried and the courage to express opinions with a strong basis, while from the aspect of conscience there are 7 data as seen from the attitudes of the figures who apply a pattern of community life based on kinship as evidenced by the attitudes of the characters who show affection for fellow citizens. In the aspect of obligation, there are 6 data which can be seen from the attitude of the leaders who show concern for fellow citizens with a sense of mutual support, respect and helping to solve problems and those that are considered burdensome among the community.